HUMAN RESOURCES COMPETENCIES IN THE INDUSTRIAL REVOLUTION 4.0 - Tigin Lugiani; Amelia Indah Pratami (STIESA Press, 2024)
Since 2015, Indonesia and other countries in the Southeast Asian region have faced the ASEAN Community. Therefore, every country, including Indonesia, must prepare human resources that have sufficient competence and are able to adapt quickly to changes to compete in the labor market in the region. Change is a must, both for individuals, companies, and the business environment. The third industrial revolution started at the end of the third century. This era is marked by the emergence of digital technology and the internet that make it easier for humans to carry out their activities and also facilitate business practices (Zeng, 2016). HR competence is the main trait that a person has so that he can work effectively and excel at work. Elements of Human Resource Development In general, there are 2 (two) main categories of training forms or methods for employees, namely: 1) Practical Methods (On The Job Training) and 2) Simulation Methods (Off The Job Training) This research was conducted to determine the competence of Human Resources in generation Z in the Industrial Revolution 4.0 era. This study uses a nonprobability sampling technique. Respondents who filled in were 36 respondents, having age criteria ranging from 18 years - 26 years. This research was conducted to determine the competence of Human Resources 4.0 in generation Z. This research uses qualitative descriptive research. The results of this study indicate that the competence of the Z generation of human resources in the era of the industrial revolution 4.0 shows a very good category with an actual score of 1943. Competence with the highest score on creative and innovative indicators with a percentage of 97.2%, the lowest score on indicators of intercultural and language abilities with a percentage 78.3%